Myths and tradeoffs : the role of tests in undergraduate admissions - Beatty, Alexandra S.; Greenwood, M. R. C.; Linn, Robert L. (Compass series (Washington, D.C.), 1999)
Admission to colleges and universities is a complex task which is made simpler by the use of test scores taken by high school students wishing to gain entrance. Though the benefits of these tests are clear this book offers recommendations to institutions of higher education and test producers to ensure that the testing is used as it should be and in the most effective ways possible.